Transfer reactions with very heavy ions - Juutinen, Sakari (1988)
This thesis deals with the reaction mechanism of the few-nucleon transfer reactions between the ⁵⁸Ni projectiles and the Dy targets. A series of transfer experiments utilizing the particle-γ coincidence technique was performed. Particle detection was used to give the scattering angles of two reaction products, and the reaction channel was selected by the discrete γ-rays in the Ge detectors. Total γ-ray energy and multiplicity distributions were measured by the Spin Spectrometer. Total γ-ray energy and multiplicity distributions, γ-ray spectra obtained by the Ge and NaI detectors and angular distributions of the projectile-like ions are discussed. For one- and two-neutron transfer the experimental results provide direct evidence of a cold mechanism populating high-spin states near the yrast line. A schematic model for the transfer mechanism is proposed. This model accounts for the prominent features of one- and two-neutron pickup.